Arctic petroleum: local CSR perceptions in the Nenets region of Russia. Issue 2 (5th June 2017) - Loe, Julia S.P.; Kelman, Ilan; Fjærtoft, Daniel B.; Poussenkova, Nina
Abstract : Purpose: The purpose of this paper is to identify and discuss perceptions of petroleum-related corporate social responsibility (CSR) among local and regional authorities, local peoples (indigenous and non-indigenous) and representatives of petroleum companies working or living in the Nenets Autonomous Okrug (NAO) in the Russian Arctic. Although the CSR literature comprises a broad spectrum of approaches, an underrepresentation of perspectives from non-business stakeholders has been suggested. The paper seeks to redress this gap. Design/methodology/approach: The data are obtained through 34 in-depth, semi-structured interviews conducted and qualitatively analysed to extrapolate perceptions, views and expectations of petroleum-related CSR in NAO. By exploring needs, wants and expectations, differences are identified between short-term expectations and long-term perspectives. Findings: A central feature of the authors' findings is the wide variation in the responses not only between community groups and sectors but also within them. The complexity identified is an argument in favour of local involvement to understand local contexts and suggests avoiding "one-size fits all" CSR approaches. Challenges and opportunities are identified for the petroleum companies in dealing with different stakeholders and diverging interests. Research limitations/implications: The importance of local context means that caution is advised when considering the transferability or generalisability of lessons, within NAO and elsewhere in and outside the Russian Arctic. Furthermore, fundamental motivations are not always transparent from interviews. Originality/value: Although a rich literature exists on CSR, this is perhaps the first study providing a cross-sectoral analysis of people's perceptions, including those of non-business stakeholders, in this region.